2016
DOI: 10.1109/jmems.2016.2554358
|View full text |Cite
|
Sign up to set email alerts
|

Polysilicon Thin Film Developed on Flexible Polyimide for Biomedical Applications

Abstract: Flexible pressure and thermal sensors are the critical parts of the functional electronic skin of prostheses and robots, as well as flexible catheter/devices for multimodal biomedical monitoring. In this paper, a polysilicon thin film was developed on a flexible polyimide substrate using aluminum induced crystallization process for biomedical pressure and temperature sensing applications. The formation of polycrystalline structure was verified from the developed polysilicon film. Long term stability and real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Both of these problems must be addressed to produce a reliable product. In this regard, Xiao et al improved the process by using a liquid PI spin coating process and introducing a polydimethylsiloxane (PDMS) intermediate layer between the silicon layer and the PI substrate [Figure 16G], thus making up for the deficiency of the traditional process [92] . Gandla et al directly integrated a flexible printed circuit board into PI film by laser-induced carbonization to make a flexible temperature sensor [Figure 16H], which fundamentally solved the problems existing in the traditional process, and further designed a flexible patch biological temperature sensor that can be applied in practice [16] .…”
Section: Temperature Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these problems must be addressed to produce a reliable product. In this regard, Xiao et al improved the process by using a liquid PI spin coating process and introducing a polydimethylsiloxane (PDMS) intermediate layer between the silicon layer and the PI substrate [Figure 16G], thus making up for the deficiency of the traditional process [92] . Gandla et al directly integrated a flexible printed circuit board into PI film by laser-induced carbonization to make a flexible temperature sensor [Figure 16H], which fundamentally solved the problems existing in the traditional process, and further designed a flexible patch biological temperature sensor that can be applied in practice [16] .…”
Section: Temperature Sensormentioning
confidence: 99%
“…In addition to being widely used in medical treatment, flexible temperature sensors have significantly contributed to mechanical temperature sensing, such as intelligent robots. On the A-C) Implantable temperature sensor which has the same thickness as a human hair [90] ; (D-F) Wearable temperature sensor [91] ; (G) The process of PDMS intermediate layer is introduced [92] ; (H) Flexible laser induction carbonation temperature sensor [16] . [93] ; (B) Relative resistance change temperature relationship of CNT composite film compared with the platinum resistance thermometer [94] ; (C and D) Temperature measurement of forehead and axilla skin surface [94] .…”
Section: Temperature Sensormentioning
confidence: 99%
“…The low mobility of a-Si compared to the values presented by other alternatives for large area fabrication on flexible substrates such as a-IGZO (>10 cm 2 V -1 s -1 ) motivated the development of low temperature polycrystalline silicon (LTPS). LTPS can be deposited on plastic substrates by PECVD [27], hot wire chemical vapour deposition (HW) [207,227], solution processes [28], aluminium induced crystallisation (AIC) [212,228], or by excimer laser annealing (ELA) of PECVD a-Si [208][209][210]. Trifunovic et al [28] deposited LTPS on paper at a maximum temperature of 150 • C by direct ELA of silicon cyclopentasilane (CPS) ink [28,229].…”
Section: Flexible Siliconmentioning
confidence: 99%
“…A highly stretchable and low-cost patch was used to monitor signals from tiny skin stretching (radial artery, blood pulses) to large scale muscle movements associated with human body motions [374]. These devices could be used to perform pressure, skin temperature [228], heartbeat [11], and blood pressure measurements [431]. Wearable textiles were studied as a potential monitoring solution of a patient's temperature [443].…”
Section: Health Monitoringmentioning
confidence: 99%
“…It has not only excellent electrical conductivity but also flexibility because of nanoscale size effects. Polycrystalline silicon film was developed on a flexible polyimide substrate using aluminum-induced crystallization process for biomedical pressure and temperature sensing applications [ 13 ]. Vaz et al reported on the development of piezoresistive Ti x Cu y thin films, deposited on polymeric substrates (PET) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%